PENYELESAIAN KONFLIK PENGELOLAAN SUMBER DAYA ALAM BERBASIS PRANATA ADAT - Sulastriyono Sulastriyono (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Conflict resolution of natural resources management is considered to be based on adat institutions when a conflict is resolved by adat law justice system in an adat forum by applying adat norms. Government, adat law community, and the private sector parties must be serious in empowering adat institutions. The seriousness of the government towards the recognition of adat intitution is outlined in the legislation. The seriousness of the adat law community is shown by receiving critically and carefully various new values that are good for strengthening the social life of the next community. The position and status of members of adat law communities are not only as a passive recipient of the local culture, but also as an actor, creator, and innovator agents of adat institutions. Members of adat law communities as active subjects carry out innovation and revitalization of adat institutions in order to adjust to the challenges of the times. The seriousness of the private sector is manifested in the willingness form of consultation with members of adat law communities to understand the feelings of the heart and the willingness of members of adat law communities.